ICOLLT 2015 - Siti Norzaimalina, Abd Majid
Kuantan – Center for Modern Languages and Human Sciences (CMLHS) has organized a conference namely International Conference on Language Learning and Teaching (ICoLLT 2015) on 1 – 3 October 2015 at Swiss Garden Beach Resort, Kuantan, Pahang. This very first international conference attracted participants from Japan, Sri Lanka, India and nearby countries like Philippines, Indonesia and Singapore. ICoLLT 2015 deemed successful since there were about 100 participants and presenters encompassed language teachers, practitioners and researchers from tertiary institutions and schools came together to share their best practices, experiences and latest research findings in language learning and teaching.